Quantitative Analysis on Force Chain of Asphalt Mixture under Haversine Loading. (30th August 2017) - Chang, Mingfeng; Huang, Pingming; Pei, Jianzhong; Zhang, Jiupeng; Zheng, Binhui
Abstract : AC-13 asphalt mixture was taken as the research object to investigate the evolution and distribution laws of force chains. A digital specimen of AC-13 asphalt mixture was reconstructed using the discrete element method (DEM) to simulate the simple performance test (SPT). Next, the force chain information among aggregate particles was extracted to analyze the evolution, probability distribution, and angle distribution of force chains. The results indicate that the AC-13 mesoscopic model reconstructed using the DEM is feasible to simulate the mesoscopic mechanical properties of asphalt mixture by comparing the predicted results and laboratory test results. The spatial distributions of force chains are anisotropic. The probability distributions of normal force chains varying with the loading times are consistent. Furthermore, the probability distribution has the maximum value at the minimum f (the ratio of contact force to mean contact force); the peak value appears again at f = 1.75 and then gradually decreases and tends to be stable. In addition, the angle distributions of force chains mainly locate near 90° and 270°, and the proportions of strong force chains are slightly greater than 50%, but the maximum proportion is only 51.12%.